Engineering transformation pathways in an Al0.3CoFeNi complex concentrated alloy leads to excellent strength–ductility combination. Issue 11 (1st November 2020) - Dasari, S.; Jagetia, A.; Soni, V.; Gwalani, B.; Gorsse, S.; Banerjee, R.
Abstract : Guided by thermodynamic modeling, engineering phase transformation pathways via thermo-mechanical processing, in a complex concentrated alloy/high entropy alloy (HEA) of composition Al0.3 CoFeNi, lead to a novel multi-scale microstructure consisting of fine-scale FCC + L12 grains mixed with B2 + BCC grains. The two-step pathway comprises initial decomposition of the parent single-phase FCC to form a fine-grained FCC + B2 microstructure, which further decomposes in the second step into the complex four-phase mixture, exhibiting an excellent combination of tensile yield stress of ∼1490 MPa, ultimate tensile strength of ∼1663 MPa, with a good ductility of ∼12% at room temperature. Impact statement: This paper reports a novel multi-phase microstructure in a HEA/CCA similar to the microstructure observed in dual-phase stainless steel. This report exemplifies the novelty of HEA/CCA compositional space. GRAPHICAL ABSTRACT: UF0001